Does exchange of information between tax authorities influence multinationals' use of tax havens? - Julia Braun; Alfons Weichenrieder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
Since the mid-1990s, countries offering tax systems that facilitate international tax avoidance and evasion have been facing growing political pressure to comply with the internationally agreed standards of exchange of tax information. Using data of German investments in tax havens, we find evidence that the conclusion of a bilateral tax information exchange agreement (TIEA) is associated with fewer operations in tax havens and the number of German affiliates has on average decreased by 46% compared to a control group. This suggests that firms invest in tax havens not only for their low tax rates but also for the secrecy they offer.
urn:nbn:de:bsz:180-madoc-388217
Keywords: F21; F23; H87; 330; tax havens; tax information exchange agreements; location decisions; international taxation